Profile of Taekwondo Achievement of Dojang Great Pioneer of the Dragon (GPD) Salatiga - Senky Aji Saputri; Rony Syaifullah; Pomo Warih Adi (PHEDHERAL, 2019)
This study aims to discover: (1) the training of taekwondo at dojang Great Pioneer of The Dragon (GPD) Salatiga in the year of 2015-2019. (2) The training program at dojang Great Pioneer of The Dragon (GPD) Salatiga in the year of 2015-2019. (3) The condition of facilities and infrastructures in supporting the achievement development of dojang Great Pioneer of The Dragon (GPD) Salatiga in 2015 – 2019. (4) The development of taekwondo achievement of dojang Great Pioneer of The Dragoon (GPD) Salatiga in 2015 – 2019. This study uses descriptive qualitative method. The data collecting method in this study is obtained through interview, observation, and document archive. The interview is conducted with the administrator and the coach. The observation is conducted directly regarding the condition of facilities and infrastructures owned by dojang Great Pioneer of The Dragon (GPD) in the year of 2015-2019. The collecting data is obtained from the document archive related with the sport achievement development of dojang Great Pioneer of The Dragon in 2015-2019. The sample collecting technique selected is by purposive and snowball sample. To find the validity of the data, it uses triangulation technique. The analysis technique used in this study is descriptive qualitative. The data obtained will be compiled and analyzed based on the variables analyzed so that obtained the overview of the taekwondo achievement development of dojang Great Pioneer of The Dragon (GPD) Salatiga in the year of 2015-2019. Based on the study results, it can be concluded that: (1) the training of taekwondo at dojang Great Pioneer of The Dragon (GPD) Salatiga year 2015-2019 has the criteria of moderate. (2) The training program at dojang Great Pioneer of The Dragon (GPD) Salatiga year 2015-2019 has the moderate criteria. (3) Dojang Great Pioneer of The dragon (GPD) Salatiga year 2015-20119 has inadequate facilities and infrastructures. (4) The achievements of dojang Great Pioneer of The Dragon (GPD) Salatiga in 2015-2019 are not always similar in every competition. However, the overall achievements of dojang Great Pioneer of The Dragon (GPD) Salatiga have experienced a great development.Profile of Taekwondo Achievement of Dojang Great Pioneer of the Dragon (GPD) Salatiga